2007
DOI: 10.1007/s11192-007-0313-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing creative scientists in nano-S&T: Productivity, multidisciplinarity, and network brokerage in a longitudinal perspective

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 14 publications
1
58
0
Order By: Relevance
“…Regarding such classification, Klavans and Boyack [29] have suggested that individual publication and citation counts can be taken as an indicator for identifying the leading researchers within a field. Similarly, other researchers suggest that citation and publication counts are obvious indicators of productive and creative scientists within a field [30][31][32]. These prolific researchers have more impact on the field, and the likelihood that these papers are selected as "creative work" is higher [33].…”
Section: Authorship Analysismentioning
confidence: 99%
“…Regarding such classification, Klavans and Boyack [29] have suggested that individual publication and citation counts can be taken as an indicator for identifying the leading researchers within a field. Similarly, other researchers suggest that citation and publication counts are obvious indicators of productive and creative scientists within a field [30][31][32]. These prolific researchers have more impact on the field, and the likelihood that these papers are selected as "creative work" is higher [33].…”
Section: Authorship Analysismentioning
confidence: 99%
“…The idea of the lone genius is criticized as a myth (Montuori, 2003) in that creativity, whilst still combining exemplary performance and rule resetting, takes place in relation to a community of practitioners and a social context that facilitates it (Amabile et al, 1996). Creative activities entail interaction within and outside the group or community (Heinze & Bauer, 2007), challenging, extending and adapting ideas and practices, dealing with and embracing the unexpected (Oliver & Roos, 2003). (We turn below to the importance of social networks functioning in creative endeavour.…”
Section: Intellectual Capitalmentioning
confidence: 99%
“…In this paper, we generally opted for the most common denominator, broker and brokerage. Notable contributions at individual or firm-level should be mentioned [5][6][7][8][9]. Most of this research builds on the ideas of brokers and structural holes [2,10,11].…”
Section: Introductionmentioning
confidence: 99%